RTHP-37. IMPACT OF 11C-METHIONINE/FDG DURAL TRACER PET-BASED, COMPARED WITH MRI-BASED TARGET DELINEATION OF MALIGNANT GLIOMAS FOR RADIATION PLANNING. (5th November 2018) - Hirata, Takero; Kinoshita, Manabu; Tamari, Keisuke; Seo, Yuji; Suzuki, Osamu; Wakai, Nobuhide; Achiha, Takamune; Umehara, Toru; Arita, Hideyuki; Kagawa, Naoki; Kanemura, Yonehiro; Shimosegawa, Eku; et al.
Abstract: Precise delineation of target volume for radiotherapy of malignant glioma is one of the crucial processes in glioma treatment. Although MRI is the modality often chosen for this procedure, the authors' previous research showed that combined use of 11C-methionine (MET) and 18F-fluorodeoxyglucose (FDG) PET was more accurate for glioma visualization (J Nucl Med, 2012). The aim of this study was to analyze volumetric and geometrical properties of RT-target-delineation based on MET/FDG PET and to compared them with those based on MRI. The impact of geometrical properties on progression free survival was further investigated. Twenty-five patients with a diagnosis of malignant glioma were included in our study. Three target volumes were compared, which included contrast-enhancing core lesions identified by contrast-enhanced T1 weighted images (T1Gd), high intensity lesions on T2 weighted images, and lesions showing high DS, a cell density score calculated from MET/FDG PET (> 3; hDS). T1Gd with 2.0 cm margin was able to cover the entire hDS only in 6 (24%) patients, indicating microscopic invasion of glioma cells beyond 2cm from gadolinium-enhanced core. Insufficient coverage of high DS region with RT target volume was suggested to be a risk for out-field recurrence. Higher coverage of hDS (T1Gd + 2/hDS) by T1Gd with 2 cm margin tended to positively impact overall and progression free survival. Cox regression analysis demonstrated that low coverage of hDS by T1Gd with 2 cm margin was predictive of tumor recurrence outside gadolinium-enhanced core, indicative of out-field reoccurrence. Present findings indicate that MRI is inadequate for target delineation for radiation therapy in malignant glioma treatment. Expanding additional margins to MRI based target volume often reduces this uncertainty while unnecessarily irradiated regions increase and MET/FDG PET seemed to provide more accurate information for target delineation than MRI.